Sequentially Vapor-Grown Hybrid Perovskite for Planar Heterojunction Solar Cells - Choi, Won-Gyu; Kang, Dong-Won; Na, Sungjae; Park, Chan-Gyu; Gokdemir, Fatma Pinar; Moon, Taeho (SPRINGEROPEN, 2018)
High-quality and reproducible perovskite layer fabrication routes are essential for the implementation of efficient planar solar cells. Here, we introduce a sequential vapor-processing route based on physical vacuum evaporation of a PbCl2 layer followed by chemical reaction with methyl-ammonium iodide vapor. The demonstrated vapor-grown perovskite layers show compact, pinhole-free, and uniform microstructure with the average grain size of similar to 320 nm. Planar heterojunction perovskite solar cells are fabricated using TiO2 and spiro-OMeTAD charge transporting layers in regular n-i-p form. The devices exhibit the best efficiency of 11.5% with small deviation indicating the high uniformity and reproducibility of the perovskite layers formed by this route.
Keywords: CH3NH3PbI3-xClx; Sequential vapor processing; Vacuum evaporation; Vapor-assisted growth; Planar Heterojunction solar cells; EFFICIENT; CH3NH3PBI3; STATE; CRYSTALLIZATION; DEPOSITION; TRANSFORMATION; TEMPERATURE; INTERFACE; UNIFORM; AIR; Science & Technology - Other Topics; Materials Science; Physics